MODEL PEMBELAJARAN PARTISPATIF BAGI MASYARAKAT DI DALAM KAWASAN HUTAN - Tahyudin, Didi; Taqwa, M. Ridhah; HP, Dadang; Alfitri, Alfitri (Publikasi Penelitian Terapan dan Kebijakan, 2014)
To improve people's access in using the resources in the surrounding forest the goverment conduct the policies. there are: village forest development policy, community forestry, forest product utilization, Timber Forest Plantation in Plantation Forest (IUPHHK-HTR) and forestry partnerships. This policy is expected to improve the incomes and welfare of the community into a better prosperous. Based on the research that has been done, it found that the people had not have the readiness of knowledge and the ability as expected. Resulting a conflict between communities with government as same as the company. Participatory learning model is an alternative to coaching, guidance and training to improve the cafacity of people in utilize forest resources properly and correctly based on the rules.